MAINTAINING CUSTOMER TRUST THROUGH CUSTOMER SATISFACTION AT PT ANEXCO MITRA ABADI - Andi Dian Putra; Agus David Ramdansyah; Meutia, Meutia (Jurnal Ekonomi, 2022)
The company cannot run its business properly without the trust of customers and the public. This study aims to determine the influence of company reputation and CRM on customer trust through satisfaction as an intervention that impacts repurchase customers of PT Anexco Mitra Abadi. The research method uses a quantitative approach with the type of survey research. The study was conducted on PT Anexco Mitra Abadi's customers with a total sample of 96 respondents using purposive sampling techniques. Based on the results of data analysis using SEM-PLS, this study shows that only six hypotheses are accepted, while one is rejected. This study concluded that the company's reputation positively and significantly affects customer trust and satisfaction. CRM was found to positively and significantly affect satisfaction and repurchase. Customer satisfaction only has a positive and significant effect on trust, but does not affect repurchases